Perencanaan Dark Heritage Bagi Masyarakat di Kawasan Pascabencana Tsunami Banda Aceh, Indonesia - Zya Dyena Meutia; Arief Rosyidie; Denny Zulkaidi; Sri Maryati (Diponegoro University, 2021)
The concept of dark heritage has been used as a concept of preserving an area or site that contains relics due to dark events in the past. The 2004 tsunami disaster that hit the city as the most affected area after the disaster has left various relics and tsunami sites that need to consider dark heritage planning. However in dark heritage planning has not yet considered aspects of local communities, especially survivors as the most affected group from the tsunami disaster. The purpose of this paper is to look at dark heritage planning that involves the community as an important aspect in the preservation of post-disaster areas as well as to find out the components and values that are considered important by the community in preserving dark heritage. The study was carried out from August 2019 to December 2019 in the post disaster area of Banda Aceh as the most affected area using a qualitative approach. This study reveals that dark heritage planning that involves communities contributes to resilience thus creating resilient communities. In addition, religion and local culture in the post disaster area are important aspects that cannot be separated for the community in sustainable dark heritage planning.